The Impact of Globalization on Border Community in Greater Mekong Sub-region (GMS): The Emergence and Response to Chinese Market in Mueang Houay Xai, Lao PDR. - Fhusai, Pittaya (Journal of Mekong Societies, 2013)
The purposes of this research are: 1) To study causes and factors to settle Chinese Market in Houay-Xai, Bokeo Province, Lao PDR. under globalization. 2) To study impacts and responses of government and local community on Chinese Market. 3) To study guideline under solving problem of government and people in local community under Chinese commercial extension. The findings are summarized as follow. The change of socialist in Lao PDR: Because of the end of the conflict between capitalist and socialist Counties, The Lao government had to adopt the policy of new economic mechanism in 1981. After new economic mechanism, the country was open even more to foreign investment in 1989. 2. The formation of economic cooperation in GMS. Chinese Merchants take advantage from R3E to ship Chinese products and move unskilled labour into Muang Huay Xai 3. The growth of multinational company in China: When China open country by using modernization policy , MNCs move to China because of low cost labour and big market. They produce many products and looking for new market to distribute their products such as Lao PDR. Chinese merchants used to sell high quality products but very expensive for Lao people. So, Chinese merchants had to change from high to low quality which products are cheap. In the same way, there are two kinds of low cost labour, skilled labour and unskilled labour. Skilled labour is people who have high education and get high income. The other are people who have low education and get low income. Finally, unskilled labour transforms themselves to new a career, Chinese merchants in Chinese market Lao PDR. 4. The weakness of business in Lao PDR. The local people don’t concern the idea of commercial but enjoy being farmers and government employee. Therefore, it is very easy for Chinese to get in to Lao Market.